Using best-worst scaling to inform agroecological interventions in Western Kenya - Zander, Kerstin K.; Drucker, Adam G.; Aluso, Lillian; Mengistu, Dejene K.; Fadda, Carlo; Termote, Céline; Davis, Kristin E. (Springer, 2026)
Both the demand for food and the environmental impacts of food production are estimated to significantly increase by 2050. Agroecological interventions have proven effective in facilitating the transition from current food production systems to more sustainable ones. These interventions can not only ensure more equitable food and nutritional security but also address poverty and reduce environmental impacts. As such, agroecological interventions can generate both private and public ecosystem services. Farmers play a key role in how food is produced, as the practices they use are linked with their preferences and expertise, as well as the constraints they face. Understanding farmers’ preferences for the adoption of different agroecological practices and their perceptions of the associated costs and benefits is critical to informing policies that can effectively support farmers in transitioning to more sustainable practices, including those that contribute to the generation of ecosystem services highly valued by broader society. To assess such preferences, we conducted a survey among farmers in Western Kenya which included a best-worst scaling experiment augmented by qualitative questions about the reasons for farmers’ views about the importance of the benefits arising from agroecological practices. Results show that farmers have strong preferences for adopting agroecological practices that generate private goods and are directly related to increasing productivity and food security, including improving health of household members. These may also include practices that have some public good elements as well, such as increasing agrobiodiversity. However, practices that generate broader public good benefits, including improved forest quality/coverage, reduced off-farm environmental impacts, greater community-level resilience to shocks, and improved landscape and wildlife management, were less important to farmers. Such findings can be used to inform policies that support farmer adoption of agroecological interventions best suited to different farming communities, as well as indicating the need for additional types of market-based incentives, such as through Payments for Ecosystem Service mechanisms.